2010
DOI: 10.1590/s1516-35982010001100013
|View full text |Cite
|
Sign up to set email alerts
|

Estimativas de parâmetros genéticos para características de crescimento em bovinos da raça Canchim utilizando modelos de dimensão finita

Abstract: RESUMO -Os objetivos neste trabalho foram avaliar diferentes modelos, em relação aos efeitos maternos considerados, para características de crescimento e estimar os parâmetros genéticos para essas características em bovinos da raça Canchim, por meio de análises uni, bi e multicaracterísticas. As características peso ao nascimento, peso ao desmame, pesos padronizados para 12, 18, 24 e 30 meses de idade em machos e fêmeas e peso adulto de fêmeas foram analisadas utilizando-se quatro modelos com os efeitos aleató… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
10
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 26 publications
7
10
1
1
Order By: Relevance
“…Likewise, the phenotypic variance (σ 2 p ) also increased almost linearly with age in both models. This finding agreed with the results of Marques et al (1999), Baldi-Rey et al (2010), Menezes (2010) and Boligon et al (2010), who reported a similar linear behavior for other beef cattle breeds.…”
Section: Resultssupporting
confidence: 92%
“…Likewise, the phenotypic variance (σ 2 p ) also increased almost linearly with age in both models. This finding agreed with the results of Marques et al (1999), Baldi-Rey et al (2010), Menezes (2010) and Boligon et al (2010), who reported a similar linear behavior for other beef cattle breeds.…”
Section: Resultssupporting
confidence: 92%
“…The observed average for bodyweight, reproductive, and carcass traits (Table 2) are in agreement with previous studies of the Canchim breed (Andrade et al 2008;Baldi et al 2010;Barichello et al 2010;Buzanskas et al 2010;Meirelles et al 2010;Borba et al 2011). The variance components and heritabilities estimated in single-trait analyses are presented in Table 3.…”
Section: Resultssupporting
confidence: 89%
“…A substantial proportion of the variation in the bodyweights, scrotal circumferences and carcass traits was associated with the additive genetic term indicating that these traits may respond to selection in Canchim cattle. For BW, WW, YW, and SCW the direct heritability estimates were in the range found in the literature for the Canchim breed, which ranged from 0.25 to 0.41 (BW), 0.23 to 0.48 (WW), 0.24 to 0.29 (YW), and 0.17 to 0.52 (SCW) (Alencar et al 1993;Silva et al 2000;Gianlorenço et al 2003;Andrade et al 2008;Baldi et al 2010;Buzanskas et al 2010;Borba et al 2011). Direct heritability estimates for BW obtained by Boligon et al (2011), El-Saied et al (2006), and Meyer (1995) were equal to 0.30 AE 0.01, 0.36 AE 0.04, and 0.38 for Nellore, Charolais, and Australian Angus cattle.…”
Section: Resultssupporting
confidence: 53%
“…Starting at this age, a new and more marked increase in these variances occurred (Figure 3). Baldi et al (2010b) and Menezes (2010) obtained linear increasing in the estimates of residual variances along the growth trajectory. In RRM, the same behavior reported in MTM was observed.…”
Section: Resultsmentioning
confidence: 94%
“…Several studies in beef cattle have demonstrated the importance of including maternal effects in the analysis (Meyer et al, 1993;Baldi et al, 2010b;Nobre et al, 2009;Menezes, 2010). Meyer (1997) reported that the models that rule out maternal effects lead to overestimates of direct heritability.…”
Section: Resultsmentioning
confidence: 99%